Evaluation of skeletal maturation in individuals with cleft lip and palate - Uslu-Akcam Ozge (Sciendo, 2017)
The assessment of hand-wrist films to identify skeletal maturation stage is a commonly used method for the determination of the status of a growing patient. However, there is limited information available regarding skeletal growth evaluation in subjects with a unilateral cleft lip and palate (UCLP). Therefore, the current study aimed to examine skeletal and chronological ages in subjects with a UCLP for comparison with those of a non-cleft control group to derive clinical guidelines.